2020
DOI: 10.1002/minf.202000102
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Ionic Liquids Toxicity against Leukemia Rat Cell Line IPC‐81 based on the Empirical‐like Models using Intuitive and Explainable Fingerprint Descriptors

Abstract: Ionic liquids as green solvents have been paid extensive attention in recent years. However, mostly it is cost and time-consuming to measure their properties. Thus, theorical methods, especially ultrafast chemoinformatics methods were introduced into these studies. Instead of abstract and complex models in some QSPR studies, in this study, the 2D structural features related to the toxicity of ionic liquids were discussed at first, and then the corresponding intuitive and meaningful descriptors were suggested t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The QSPR model has been proposed for the evaluation of the melting temperature of the imidazolium ILs [ 229 ]. The quantitative structural-activity relationship studies (QSAR) have been used for predicting the toxicity against human HeLa and MCF-7 cancer cell lines [ 230 ], the leukemia rat cell line (IPC-81) [ 231 , 232 ]. Zhu et al [ 233 ] elaborated quantitative structure-activity relationships (QSAR) models using an extreme learning machine (ELM) algorithm to evaluate the toxicity of ILs toward the acetylcholinesterase enzyme.…”
Section: Design Of Environmentally Harmless Ilsmentioning
confidence: 99%
“…The QSPR model has been proposed for the evaluation of the melting temperature of the imidazolium ILs [ 229 ]. The quantitative structural-activity relationship studies (QSAR) have been used for predicting the toxicity against human HeLa and MCF-7 cancer cell lines [ 230 ], the leukemia rat cell line (IPC-81) [ 231 , 232 ]. Zhu et al [ 233 ] elaborated quantitative structure-activity relationships (QSAR) models using an extreme learning machine (ELM) algorithm to evaluate the toxicity of ILs toward the acetylcholinesterase enzyme.…”
Section: Design Of Environmentally Harmless Ilsmentioning
confidence: 99%
“…Therefore, the SVM model can generally provide more accurate predictions on the toxicity of ILs against IPC-81, which confirms the conclusion obtained from Figure 7. The two ML models established in this work were compared with the reported models developed by Sosnowska et al [18] and Wu et al [19]. As shown in Table 1, the FNN and SVM models presented much lower RMSE and MAE as well as a much higher R 2 value than the two previous models, indicating their higher predictive accuracy.…”
Section: Model Comparisonmentioning
confidence: 77%
“…Due to the utilization of a larger database, this model, in principle, shows improved applicability. Based on this updated dataset, Wu et al [19] recently reported another MLR model using IL fingerprint descriptors, which resulted in an improved predictive accuracy (MAE = 0.34). Despite the effectiveness of MLR, there is still a large potential for the further improvement of model accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…Some examples of studies concerning the prediction of toxicity for selected chemicals as potential pollutants are summarized in Table 3. One of the most frequently predicted environmental parameters is toxicity, which may be noticed due to the visible trend in IL properties' prediction analysis as summarized above [74][75][76][77]. It is expressed by different endpoints towards various organisms.…”
Section: Properties (Prediction and Correlation)mentioning
confidence: 99%